How the use of an online healthcare community affects the doctor-patient relationship: An empirical study in China - Wang, Zhanyou; Zhang, Xin; Han, Dongmei; Zhao, Yaopei; Ma, Liang; Hao, Feifei (Frontiers in Public Health, 2023)
Possible improvements to the doctor-patient relationship are an important subject confronting national healthcare policy and health institutions. In recent years, online healthcare communities have changed the ways in which doctors and patients communicate, especially during the COVID-19 pandemic. However, previous research on how usage of online healthcare communities has affected the doctor-patient relationship is rather limited. This paper proposes a research model to investigate the relationship between online healthcare community usage and the doctor-patient relationship. An analysis of 313 patients' data using structural equation modeling showed the following. First, the use of an online healthcare community has a positive impact on doctor-patient communication, helps improve the performance of healthcare procedures, and reduces healthcare costs. Second, doctor-patient communication and healthcare costs have a positive impact on patients' emotional dependence and patients' perception of healthcare quality, while healthcare procedures do not have this impact. Finally, patients' emotional dependence and perception of healthcare quality have a positive effect on doctor-patient relationship through the mediator of patients' satisfaction.